Protecting group principles suited to late stage functionalization and global deprotection in oligosaccharide synthesis. (November 2022) - Dhara, Debashis; Dhara, Ashis; Murphy, Paul V.; Mulard, Laurence A.
Abstract: Chemical synthesis is a powerful tool to access homogeneous complex glycans, which relies on protecting group (PG) chemistry. However, the overall efficiency of chemical glycan assembly is still low when compared to oligonucleotide or oligopeptide synthesis. There have been many contributions giving rise to collective improvement in carbohydrate synthesis that includes PG manipulation and stereoselective glycoside formation and some of this chemistry has been transferred to the solid phase or adapted for programmable one pot synthesis approaches. However, after all glycoside bond formation reactions are completed, the global deprotection (GD) required to give the desired target OS can be challenging. Difficulties observed in the removal of permanent PGs to release the desired glycans can be due to the number and diversity of PGs present in the protected OSs, nature and structural complexity of glycans, etc. Here, we have reviewed the difficulties associated with the removal of PGs from densely protected OSs to obtain their free glycans. In particularly, this review focuses on the challenges associated with hydrogenolysis of benzyl groups, saponification of esters and functional group interconversion such as oxidation/reduction that are commonly performed in GD stage. More generally, problems observed in the removal of permanent PGs is reviewed herein, including benzyl, acyl (levulinoyl, acetyl), N-trichloroacetyl, N-2, 2, 2-trichloroethoxycarbonyl, N-phthaloyl etc. from a number of fully protected OSs to release the free sugar, that have been previously reported in the literature. Graphical abstract: Image 1 Highlights: Permanent protecting group selection in oligosaccharide (OS) synthesis can be challenging. Global deprotection (GD) is an essential part in the chemical synthesis of complex OS which can meet unexpected challenges. Hydrogenolysis of complex OSs may turn into a major bottleneck, due to reproducibility issues and undesired side products.